Experimental study on Empty Fruit Bunch (EFB) composite subjected to three point bending using ANOVA technique - Zulkepli, I.I.; Mokhtar, Hanan; Shaik Dawood, Mohd. Sultan Ibrahim; Aminanda, Yulfian; Mohamed Rehan, Muhammad Saifuddin (The Mattingley Publishing Co., Inc., 2020)
This study focuses on the evaluation of factor effect to obtain the optimum configuration on empty fruit bunch (EFB) composite for impact purposes performed by statistical analysis using light resin transfer molding (LRTM). Three factors considered in this study are resin pressure, EFB volume fraction and EFB composite thickness. There are three levels of factorial design and two factors that have been developed to relate between ultimate strength and young’s modulus. Identification on the analysis of variance (ANOVA) was applied to achieve the most influential factors on responses and optimum configuration. All the three considered factors influence the composite performance although only two are considered as the most influential factors on the composite performance for impact purposes.